EFFECT OF SEX, SEASON, AND SIZE ON THE CHEMICAL COMPOSITION OF RED SEA GOATFISH Parupeneus forsskali (Fourmanoir and Guézé, 1976) CAUGHT FROM THE MARINE WATER OF LATTAKIA GOVERNORATE (SYRIA) - BARAKAT, ISSA; SAAD, ADIB; NISAFI, IBRAHIM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The effects of seasonal and sexual differences and Total Lenght on the chemical composition of the Red Sea goatfish Parupeneus forsskali caught from the marine waters of Lattakia Governorate were investigated. Moisture, crude protein, crude fat, and ash were determined as a percentage of the fish muscles. The results revealed that the autumn season was the highest in terms of nutritional components (protein 22.08%, fat 9.78%, ash 2.42% of fresh fish muscle), While the Summer season was the lowest (protein 19.32%, fat 5.46%, ash 1.20%). The results also showed the superiority of females in the values of the nutritional components over males, where the values were for females (protein 22.3%, fat 8.9%) and males (protein 20.7%, fat 6.8%), while The results also showed the superiority of males in the values of ash over females of ash (male 1.5%, female 1.3%). Regarding the body length factor, the results showed a significant positive relationship between an increase in Total length and an increase in protein and fat and a significant inverse relationship with both ash and moisture content.